Potensi Arkeologi di Pulau Alor - I Nyoman Rema; Hedwi Prihatmoko (KALPATARU, 2016)
Abstract. Alor is one of the outer islands in Indonesia bordered with Democratic Republic of Timor Leste which has numerous significant cultural heritages from the past, from megalithic tradition to the development of major religions in Indonesia. This article is written to share about archaeological potentials in Alor island which can be developed to strengthen national identity, patriotism, and improve the prosperity of Alor community. The data of this research was collected through literature reviews. The completed data was then managed using descriptive-qualitative method by defining the archaeological remains, the function, and the meaning based on the result of the research, then to sum it up, a conclusion. Some archaeological potentials in this island are misba, traditional houses, moko, bulding structures, old Quran, burial urns, and mystical-growing pots. Those archaeological potentials prove that Alor community still upholds their high cultural values and also become a communication media that establishes a harmony with God, humans, and environment.Abstrak. Alor merupakan salah satu pulau terluar Indonesia yang berbatasan dengan Negara Republik Demokratik Timor Leste dan memiliki berbagai tinggalan budaya penting dari masa lampau, berupa tradisi megalitik hingga berkembangnya agama-agama besar di Nusantara. Tulisan ini bertujuan mengetahui potensi arkeologi di Pulau Alor, yang kemudian perlu dikembangkan untuk memperkuat karakter dan jati diri, cinta tanah air, dan meningkatkan kesejahteraan masyarakat Alor. Data penelitian ini dikumpulkan melalui studi pustaka. Setelah data terkumpul, pengolahan dilakukan secara descriptif-kualitatif dengan mendeskripsikan tinggalan arkeologi, fungsi dan maknanya berdasarkan hasil penelitian yang kemudian diakhiri dengan penyimpulan. Potensi tinggalan arkeologi di pulau ini berupa misba, rumah adat, moko, struktur bangunan, Al Quran kuno, kubur tempayan, kubur ceruk, dan periuk tumbuh. Berbagai potensi arkeologi tersebut membuktikan tingginya nilai peradaban masyarakat Alor, sekaligus sebagai media komunikasi dalam membangun hubungan harmonis dengan Tuhan, sesama, dan lingkungannya.